Programa Município Verde Azul na Gestão da Arborização Urbana em Araraquara e São Carlos, SP - Nespolo, Cássia Conceição da Cruz (2020)
The theme of Arboriculture in Brazil presents itself as a research field that covers multiple areas of knowledge and diverse professional practices and activities. It is around this issue that this master's research is based: in seeking to analyze an experience, considered innovative, in the theme of management of Arboriculture in Brazil, specifically in the State of São Paulo, with the Municipality Program Verde Azul - MPVA. Research carried out on the MPVA highlights that there are few studies dedicated specifically to the Arboriculture Directive - AD. The general objective of this research was to investigate, what is the influence of the MPVA’s AD on the current Arboriculture management of the municipalities of Araraquara and São Carlos, SP. Checking the municipal actions carried out in the years 2017 and 2018 and the perception of the interlocutors regarding the fulfillment of the criteria and the current experience with the AD. An exploratory qualitative approach was used, based on the case studies of Araraquara and São Carlos. The methodological procedures were: bibliographic research, documentary research and semi-structured interviews. The documents and interviews were explored and analyzed by means of content analysis techniques, seeking to extract as much information as necessary to fulfill the specific objectives of this research. The actions carried out by the municipalities to comply with the AD are still very fragmented by criteria, with the need for planning urban afforestation in the municipality in a prior and integrated way. However, it was noted that AD mobilized actions aimed at Urban Tree Management in the municipalities studied. The set of actions that have been mobilized by AD, aims to strengthen the management and management in relation to Arboriculture at the municipal scale and are part of the MPVA's objective to improve the environmental efficiency of the São Paulo municipalities. It was concluded that AD has influenced the current Arboriculture Management of the municipalities studied.